La Iglesia y las Cortes de Cádiz - Higueruela del Pino, Leandro (Cuadernos de Historia Contemporánea, 2002)
The clergy outstanding role in Cortes de Cádiz is due, not only because of the big number of deputies being Catholic ministers but also to their cultural and political significance. The steps taken in connection with ecclesiastic reforms respond to the moment war circumstances as well as to the press opinion. Official recognition of Catholic Religion, Inquisition suppression, regular clergy reform, among other decisions, have this mark. Anyway, regalismo, in its way of acting, takes a position of realism and political moderation.